2017
DOI: 10.1002/jctb.5269
|View full text |Cite
|
Sign up to set email alerts
|

Optimized purification of mono‐PEGylated lysozyme by heparin affinity chromatography using response surface methodology

Abstract: BACKGROUND: The efficient, controlled and robust purification of conjugates from PEGylation has a growing demand in the biopharmaceutical's market. In general, the yield and purity reached through the conventional chromatographic modes are not particularly high or efficient. Affinity chromatography has so far scarcely been explored. The present work introduces the purification of mono-PEGylated lysozyme from a PEGylation reaction by heparin affinity chromatography (HAC) for the first time in a single step. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The protein mixture tested at condition A (flow at 0.8 mL min ‐1 and 13 CVs, Fig. (A)) represents lysozyme PEGylation separation at the optimal conditions for the purification of mono‐PEGylated lysozyme using a linear salt gradient found by our group in a previous study . The relative error for the retention time of native lysozyme in mixture A (0.51%) was lower than that in the individual standard (1.62%), while for the mono‐PEGylated lysozyme the error increased slightly (0.87 vs 1.41%).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…The protein mixture tested at condition A (flow at 0.8 mL min ‐1 and 13 CVs, Fig. (A)) represents lysozyme PEGylation separation at the optimal conditions for the purification of mono‐PEGylated lysozyme using a linear salt gradient found by our group in a previous study . The relative error for the retention time of native lysozyme in mixture A (0.51%) was lower than that in the individual standard (1.62%), while for the mono‐PEGylated lysozyme the error increased slightly (0.87 vs 1.41%).…”
Section: Resultsmentioning
confidence: 85%
“…In our study, di‐PEGylated lysozyme was not included in the PEGylation protein mixture because in our previous work this protein was shown not to be retained in the heparin support at dynamic conditions and it was also shown that a mixture of mono‐PEGylated lysozyme and native lysozyme in a 4:1 ratio represents the separation observed in a lysozyme PEGylation reaction. Presently, model predictions based on pure proteins provide a good approximation to the real separation …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations